Applying capture recapture methods to estimate the burden of chlamydial and gonococcal infections using Indian Health Service Medical Records, 2016-2021. - Haberling, Dana L; Ge, Lin; Pondo, Tracy; Taylor, Melanie M; Nuorti, J Pekka; Apostolou, Andria (American Journal of Epidemiology, 2026)
American Indian and Alaska Native persons in the United States experience high rates of chlamydia and gonorrhea (CT/GC) infections, but the burden among persons receiving healthcare through the Indian Health Service (IHS) has not been recently described. Currently, there is no surveillance system to regularly monitor IHS-specific CT/GC burden and trends. We used two capture recapture (CRC) methods with two IHS medical records sources: diagnostic codes and laboratory test results linked by person within 30 days among persons ≥15 years during 2016 to 2021. Capture recapture estimates were used with the IHS population to create prevalence rates and compared to the medical records counts. CRC estimated 88 680 (1189 per 100 000) and 83 884 CT infections (1125) and 36 713 (492) and 35 930 GC infections (482). Diagnostic codes were 60% and 63% of CT and 54% and 56% of GC CRC estimates and combined with laboratory test results were 88% and 94% of CT and 86% and 88% of GC CRC estimates. These findings underscore the value of IHS medical records for estimating CT/GC infections and measuring undercounting of single source CT/GC medical records. These sources can be leveraged to provide surveillance estimates for monitoring trends; strategic outreach; and supporting testing, treatment, and staffing needs.